CLASSPOINT TO INCREASE STUDENTS’ ENGLISH LEARNING MOTIVATION - Bangsa, Ade Fitriani Kesuma; Korompot, Chairil Anwar; Muhayyang, Maemuna (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This pre-experimental study evaluated (1) the impact of ClassPoint, an interactive learning media on students' English learning motivation and (2) found the main components of motivation that were significantly affected by the use of ClassPoint. A scaled test conducted with a questionnaire was used to collect data. Questionnaires were distributed to students of class VIII.A UPT SPF SMPN 40 Makassar to find out students' English learning motivation before and after treatment.  Total of 34 students of class VIII.A were sampled in this study. The results of descriptive statistics showed that the average score of students' motivations increased significantly from 31.41 in the pre-test to 54.94 in the post-test. The t-test results showed (1) a significant difference in student motivation (Y) before and after using ClassPoint (X), with a significance value of 0.000. In addition, the N-Gain value of 1.51 indicates a substantial increase in student motivation, which places it in the high classification category. (2) learning goals were the most influential indicator, with an increase of 99%. This finding showed that ClassPoint is highly effective in increasing student motivation, especially in terms of learning goals. These results reinforce the theoretical support for the constructivist learning theory, showing that interactive media like ClassPoint significantly enhance student motivation, while also offering practical implications for educators to adopt this technology to achieve more effective learning outcomes.